Examining gender diversity growth as a model for inclusion of all underrepresented persons in medical physics. Issue 12 (12th November 2020) - van Zyl, Maxine; Haynes, Elijah M. K.; Batchelar, Deidre; Jakobi, Jennifer M.
Abstract : The labor force of Medical Physics is one of the most gender diverse in the field of Physics, as it has attained the proportional achievement of ~30% women worldwide (Tsapaki et al. Phys Medica . 2018;55:33–39). While great strides have been made toward a gender diverse workforce, women still comprise an underrepresented group. Many strategies have been suggested to increase the participation of underrepresented persons by addressing unconscious biases, increasing opportunities, dedicated hiring policies, and providing support networks in science and medicine (Barabino et al. Sci Eng Ethics . 2019; Coe et al. Lancet . 2019), yet the personnel landscape remains largely uniform. Herein, the conditions, strategies, and approaches that facilitated gender diversity in Medical Physics are considered as a means to further the inclusion of other underrepresented groups through exemplars of mentorship, addressing unconscious biases and the implementation of inclusive practices. Furthermore, the potential for gender diversity to act as a catalyst to create an environment that is more accepting of diversity and supports and encourages inclusive practices for the participation and inclusion of other underrepresented groups in Medical Physics is discussed.